Exploring Environmental Factors Associated with Child Wellbeing during COVID-19 in Australia and Germany - Penny Levickis; Lisa Murray; Frank Niklas; Lynn Lee-Pang; Marius Vogt; Jane Page; Patricia Eadie; Simone Lehrl (MDPI AG, 2023)
The COVID-19 pandemic has had a significant impact on the wellbeing of children and families globally. With extended lockdown periods, early childhood education and school closures, and remote learning, families experienced increased stress and anxiety, financial hardship, and disrupted routines. This paper aims to explore associations between children's social-emotional wellbeing and environmental factors (including the burden of COVID-19 on the family, early learning experiences in the home and early childhood education, and parent wellbeing and mental health) during COVID-19 in Australia and Germany, two countries that experienced significant lockdown periods. Using a longitudinal online survey design, parents of young children (aged 1-6 years) in Australia (N = 66) and Germany (N = 53) completed surveys on their own wellbeing; their child's wellbeing; the home learning environment, and their satisfaction with early childhood education and care at two time points in 2020 and 2021. The burden of COVID-19 mitigation measures on families' everyday lives correlated with child wellbeing outcomes in both the Australian and German cohorts. Findings also provide evidence of potential protective factors of children's social-emotional wellbeing during stressful events, such as the lockdowns experienced by families in Germany and Australia during the pandemic.